[T]read Between the Lines Unraveling and Upskilling Hidden Communities in Orange Grove and Norwood - Moshe, Khumo (University of the Witwatersrand, Johannesburg, 2023)
This research explores the historical tension and socio-economic differences between Orange Grove and Norwood, which are neighbouring suburbs characterized by a diverse culture and a mixed-income profile. These tensions lie between and along major arterial nodes Louis Botha Avenue and Grant Avenue, which serve communities. Louis Botha Avenue is a transit route and Grant Avenue, is a local retail high street. The study investigates the potential of Patterson Park, located between Louis Botha and Grant Avenue, as a mediating space for these neighbourhoods. The park offers the opportunity for connection between these neighbourhoods through urban principles that create safe and comfortable public connections. The proposed intervention neighbours Paterson Park and is driven by the imitiate human interactions. It aims to establish a maker’s guild and trade training centre, providing opportunities and possibilities for marginalized individuals, local entrepreneurs, businesses, and the community. The facility will impart essential urban principles for successful neighbourhoods and emphasize the significance of public art, craft in construction, along with facilitating better contractor-client relationships.
A research report submitted in fulfillment of the requirements for the Masters in Architecture, In the Faculty of Engineering and the Built Environment, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; tread; walkable cities; skills developmen; place-making; SDG-4: Quality education; SDG-8: Decent work and economic growth